Study of Factors Influencing Traffic Violations in Jakarta: Perspective of the Theory of Planned Behavior (TPB) in the Implementation of Electronic Traffic Law Enforcement (ETLE) - Ruci, Khobat Dewa; Soehodho, Sutanto; Sumabrata, R. Jachrizal (UI Scholars Hub, 2024)
Transportation safety in Indonesia reflects its culture and modernity, but the high rate of traffic accidents indicates significant challenges. Data from IRSMS and Polda Metro Jaya reveal an increase in accidents and traffic violations, reinforcing the need for effective law enforcement. The implementation of ETLE, supported by Law No. 22 of 2009 on Road Traffic and Transportation and Law No. 19 of 2016 on Electronic Information and Transactions, is a strategic effort to improve law enforcement. However, its effectiveness in Jakarta context still requires in-depth evaluation. This thesis focuses on the psychological factors in the use of ETLE using the Theory of Planned Behavior. The analysis results show that factors such as self-confidence, anxiety, and influence of other drivers significantly contribute to the tendency of violations. With a beta coefficient of 0.029 and a t-statistic of 15.776, a holistic approach to road safety is required, involving infrastructure, law enforcement, driving education, and psychological aspects, to achieve the WHO target of reducing accidents by 50% in the Decade of Action for Road Safety 2021-2031.